2005
DOI: 10.1056/nejmoa050373
|View full text |Cite
|
Sign up to set email alerts
|

Febuxostat Compared with Allopurinol in Patients with Hyperuricemia and Gout

Abstract: Febuxostat, at a daily dose of 80 mg or 120 mg, was more effective than allopurinol at the commonly used fixed daily dose of 300 mg in lowering serum urate. Similar reductions in gout flares and tophus area occurred in all treatment groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
888
4
45

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,132 publications
(1,001 citation statements)
references
References 31 publications
36
888
4
45
Order By: Relevance
“…The relatively high dropout rate was mainly due to the design of the study (cohort) in combination with the sudden need for alternative treatment. On the other hand, we found a mean relative decrease in sUr of 61% for benzbromarone and 36% for allopurinol, which corresponds well with values published in the literature of 54-58% for benzbromarone 80-125 mg/day and 27-44% for allopurinol 300 mg/day in patients not previously treated with benzbromarone [5,15,16,23,24].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The relatively high dropout rate was mainly due to the design of the study (cohort) in combination with the sudden need for alternative treatment. On the other hand, we found a mean relative decrease in sUr of 61% for benzbromarone and 36% for allopurinol, which corresponds well with values published in the literature of 54-58% for benzbromarone 80-125 mg/day and 27-44% for allopurinol 300 mg/day in patients not previously treated with benzbromarone [5,15,16,23,24].…”
Section: Discussionsupporting
confidence: 88%
“…Reported events were rash, pruritus, diarrhoea, nausea and dizziness, which are all well-known side effects of allopurinol. Becker et al [23] found a similar rate (12%) of adverse events related to allopurinol.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The proportion of patients with gout flares requiring treatment declined over 52 weeks, similar to that observed in other studies with febuxostat or allopurinol 5, 6, 8. Longer‐term treatment may be needed to further reduce gout flares, as well as to dissolve baseline tophi, particularly to demonstrate treatment effect differences 24, 25.…”
Section: Discussionsupporting
confidence: 75%
“…A treat-to-target serum urate (SU) strategy for gout patients with an indication for urate-lowering therapy (ULT) has been widely endorsed as a means of optimizing clinical outcomes. Achievement of an SU ,6.0 mg/dl has been associated with improved outcomes, including reductions in gout flare frequency and tophi (2)(3)(4)(5)(6)(7). Thus, multiple international guidelines support the adoption of such a treatment target (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%